Urethral Reconstruction Combined with Modified Urethrostomy in a Cat after Prepubic Urethrostomy - Kim, Kihoon; Kim, Jaehwan; Kim, Hwi-Yool (Acta Scientiae Veterinariae, 2022)
Background: In cats, urethral obstruction is generally caused by various reasons, including feline idiopathic cystitis, urethral crystals, urethral trauma, mucous plug, congenital or acquired anatomical deformity, and urolithiasis, especially in male cats. Depending on the severity and duration of clinical signs, immediate management including conservative or surgical therapy for restoration of urethral patency is required. Repetitive urethral obstruction due to intraluminal plugs, obstruction that cannot be resolved by medical management, and urethral strictures, trauma, or neoplasia should be managed by surgery. When the penile or pelvic urethra is ruptured or not long enough to mobilize the pelvic urethra to the perineal skin by repetitive perineal urethrostomy, prepubic urethrostomy is indicated. Potential complications of prepubic urethrostomy include urinary incontinence, peristomal dermatitis. In such cases, management of the peristomal site or placement of an artificial urethral sphincter have been reported previously. However, to date, urethral reconstruction using pre-existing penis has not been reported after prepubic urethral stricture following prepubic urethrostomy. The objective of this report is to describe surgical procedure of the urethral reconstruction combined with modified perineal urethrostomy in a cat with prepubic urethral stricture after prepubic urethrosotmy. Case: A 3-year-old castrated Scottish straight cat presented with dysuria after prepubic urethrostomy. The owner reported that the patient was diagnosed with urethral rupture, had undergone prepubic urethrostomy 2 months prior to presentation, and had persistent dysuria despite repetitive surgical revision of the prepubic urethral stoma at a local hospital. On physical examination, the preputial orifice and the penis appeared grossly normal. On ultrasonography, pericystic and periurethral fat had an edematous, striated appearance with alternating hyperechoic and anechoic regions. A small amount of free fluid was visible around the urethra. Abdominal radiography revealed a mildly distended bladder and loss of serosal detail around the area of the urinary bladder neck, consistent with inflammation and free fluid observed on ultrasonography. The retrograde urethrogram showed no leakage in either sites of the prepubic urethral orifice or the penis. Hence, complete urethral reconstruction with modified perineal urethrostomy was performed. The patient had normal urination at the 15-month follow-up. Discussion: Prepubic urethrostomy is beneficial for the patients whose penile or pelvic urethra is ruptured or not long enough to mobilize the pelvic urethra to the perineal. Complications of prepubic urethrostomy include skin necrosis around the stoma; urinary incontinence; stricture of the urethral stoma due to several reasons such as surgical-site irritation; poor mucosa–skin apposition; failure to provide tension-free stoma; and failure to expose wider pelvic urethra. In these cases, surgical management of the level of prepubic urethral stoma has been recommended by previous studies. However, no studies have been reported urethral reconstruction using pre-existing penile urethra in a patient with prepubic urethral stricture so far. To the author’s knowledge, this case is the first report describing urethral reconstruction in a cat with urethral stricture after prepubic urethrostomy. Keywords: cat, modified urethrostomy, prepubic urethrostomy, urethral reconstruction.